The emergence of globalism : visions of world order in Britain and the United States, 1939-1950 - Rosenboim, Or (Princeton, New Jersey : Princeton University Press, 2017)
"During and after the Second World War, public intellectuals in Britain and the United States grappled with concerns about the future of democracy, the prospects of liberty, and the decline of the imperial system. Without using the term 'globalization,' they identified a shift toward technological, economic, cultural, and political interconnectedness and developed a 'globalist' ideology to reflect this new postwar reality. The Emergence of Globalism examines the competing visions of world order that shaped these debates and led to the development of globalism as a modern political concept. Shedding critical light on this neglected chapter in the history of political thought, Or Rosenboim describes how a transnational network of globalist thinkers emerged from the traumas of war and expatriation in the 1940s and how their ideas drew widely from political philosophy, geopolitics, economics, imperial thought, constitutional law, theology, and philosophy of science. She presents compelling portraits of Raymond Aron, Owen Lattimore, Lionel Robbins, Barbara Wootton, Friedrich Hayek, Lionel Curtis, Richard McKeon, Michael Polanyi, Lewis Mumford, Jacques Maritain, Reinhold Niebuhr, H. G. Wells, and others. Rosenboim shows how the globalist debate they embarked on sought to balance the tensions between a growing recognition of pluralism on the one hand and an appreciation of the unity of humankind on the other."--Dust jacket.
Chapter 1. Inroduction: A new global order -- Drawing the contours of globalism -- The mid-century discourse of globalism -- The ideologues of globalism -- Outline of the book -- Chapter 2. Reimagining the state in a global space -- The intellectual worlds of Raymond Aron and David Mitrany -- Critique of ideology and nationalism -- The state and a new world order -- Europe, United and divided -- E. H. Carr and political order in the global age -- Chapter 3. Geopolitics and regional order -- Owen Lattimore, Nicholas J. Spykman, and the science of geopolitics -- Isaiah Bowman, Karl Haushofer, and geopolitics in transition -- Lattimore and Spykman on land, sea, and air power -- The geopolitics of scale -- After Frederick Jackson Turner: The frontier in international relations -- Tripolarity -- The geopolitics of regional democracy -- Geopolitics and the post-war political space -- Chapter 4. The end of imperial federalism? -- Federal union: Lobbying for a democratic federation -- Lionel Curtis's Sermon on the Mount -- Clarence Streit: 'We need union now' -- Frederick Lugard, Norman Bentwich, and the boundaries of the Commonwealth -- Chapter 5. Federal democracy for welfare -- Lionel Robbins and the politics of economic federalism -- Barbara Wootton's democratic plan for freedom -- Friedrich Hayek and the challenge of liberal federalism -- The emancipatory hope of democratic federalism -- Chapter 6. Writing a world constitution: The Chicago committee and the new world order -- Richard McKeon, Giuseppe Antonio Borgese, and the establishment of the Chicago committee -- The unity and division of sovereignty -- The problem of representation -- Decolonising the non-West -- Pluralism and human rights -- The preliminary draft of a world constitution -- Hans Kelsen and the critics of the constitution -- The limits of constitutionalism -- Chapter 7. Perceptions of science and global order -- World government or world destruction: H. G. Wells responds to the crisis -- Charles E. Merriam, scientific objectivity, and political judgment -- Michael Polanyi and the liberal dynamic order -- Lewis Mumford's remedy to global madness -- A turn to faith -- Chapter 8. Catholicism, pluralism, and global democracy -- Luigi Sturzo, Jacques Maritain, and democracy in exile -- Political pluralism and the challenge of order -- Maritain, Sturzo, and Aron propose federalism against Machiavellianism -- Global democracy and Catholic morality -- Global 'pluralism(s) of fear' -- Chapter 9. Conclusion: The genealogy of globalism -- The public role of intellectuals -- The globalist ideology and the globalised future.
Includes bibliographical references (pages 287-323) and index.
Keywords: Globalization -- History; Globalization -- Philosophy; International relations -- Philosophy; World politics -- 1933-1945.; World politics -- 1945-1955.